Insights into bone morphogenetic proteins in cardiovascular diseases - Ye, Di; Liu, Yinghui; Pan, Heng; Feng, Yongqi; Lu, Xiyi; Gan, Liren; Wan, Jun; Ye, Jing (Frontiers in Pharmacology, 2023)
Bone morphogenetic proteins (BMPs) are secretory proteins belonging to the transforming growth factor-β (TGF-β) superfamily. These proteins play important roles in embryogenesis, bone morphogenesis, blood vessel remodeling and the development of various organs. In recent years, as research has progressed, BMPs have been found to be closely related to cardiovascular diseases, especially atherosclerosis, vascular calcification, cardiac remodeling, pulmonary arterial hypertension (PAH) and hereditary hemorrhagic telangiectasia (HHT). In this review, we summarized the potential roles and related mechanisms of the BMP family in the cardiovascular system and focused on atherosclerosis and PAH.